Preparation method of copper tungstate photo-anode film, copper tungstate photo-anode film and application
By introducing gradient-doped molybdenum elements into the copper tungstate photoanode film, the problems of poor charge transport performance and high electron-hole recombination rate in photoelectro-catalytic water decomposition are solved, and higher photoelectrocatalytic performance and stability are achieved.
Patent Information
- Application Number
- CN202411786809.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-04
AI Technical Summary
The existing copper tungstate photoanode materials have poor charge transport performance and high electron-hole recombination rate in photoelectro-catalytic water decomposition, which limits their efficiency and stability.
By introducing gradient-doped molybdenum elements into the copper tungstate photoanode film, adjusting their conductive position and energy band structure, a continuous gradient energy level structure is formed, thereby improving the separation efficiency of electron-holes.
The photoelectro-catalytic performance of the copper tungstate photoanode film is significantly improved, including improving the photocurrent density and overall photoelectric conversion efficiency, and enhancing the conductivity and stability of the film.
Smart Images

Figure CN119753677A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of clean energy, and in particular relates to a preparation method of a copper tungstate photoanode film, the copper tungstate photoanode film and applications. Background Art
[0002] With the gradual depletion of fossil energy and the environmental pollution problems caused by its use. Clean energy, especially hydrogen energy, has become one of the research hotspots in the energy field due to its environmental protection and high efficiency. There are many ways to obtain hydrogen energy, among which hydrogen production through photoelectrocatalytic water decomposition is considered to be one of the most promising technologies. Photoelectrocatalytic water decomposition uses solar energy as a driving force to produce hydrogen from water. It has the advantages of being green, sustainable, and widely distributed. Especially in the context of increasing global attention to reducing greenhouse gas emissions, solar photocatalytic hydrogen production technology provides a feasible way to solve energy problems. Studies on many photoanode materials have shown that copper tungstate (CuWO4), as a ternary metal oxide, has become a candidate material that has attracted much attention in the field of photoelectrocatalytic hydrogen production because of its suitable band gap, high theoretical photocurrent density, and good stability.
[0003] The application of CuWO4 in photoelectrocatalytic water splitting is mainly due to its moderate band gap (about 2.2eV), which enables it to effectively absorb visible light and convert it into electrons and holes, thereby driving the water splitting reaction. In addition, the theoretical photocurrent density of CuWO4 is relatively high, about 10.7mA / cm 2 , this value makes it have a higher energy conversion efficiency in theory. More importantly, CuWO4 exhibits good chemical stability, can maintain stable catalytic performance for a long time under certain conditions, adapt to the acid-base environment in the water decomposition process, and has certain application prospects. However, although CuWO4 has excellent catalytic performance in theory, there is a significant performance gap in its practical application. The root of this problem lies mainly in its poor charge transfer performance and high electron-hole recombination rate, both of which limit its efficiency and stability in photocatalytic reactions. Therefore, how to improve the photoelectrocatalytic performance of the CuWO4 photoanode has become a problem that needs to be solved at present. It is hoped that a copper tungstate photoanode film with better photocatalytic performance and higher stability can be developed to promote the practical application of photoelectrocatalytic water decomposition hydrogen production technology and help the widespread application and promotion of clean energy. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a method for preparing a copper tungstate photoanode film. The copper tungstate photoanode film prepared by the method has molybdenum doped in a gradient manner. The introduction of molybdenum helps to reduce the conductive position of copper tungstate, and the continuous concentration change makes a continuous gradient energy level structure appear in the bulk phase of the film. Therefore, the performance of the doped film is greatly improved compared with the undoped and uniformly doped copper tungstate photoanode materials.
[0005] The invention also provides a copper tungstate photoanode film.
[0006] The invention also provides application of the copper tungstate photoanode film in photoelectrocatalytic water decomposition.
[0007] The first aspect of the present invention provides a method for preparing a copper tungstate photoanode film, comprising the following steps:
[0008] S1: using a copper source, a tungsten source and a molybdenum source to prepare a solution containing copper, tungsten and molybdenum, and adjusting the pH of the solution;
[0009] S2: placing the substrate obliquely in a reaction kettle containing the solution, sealing it, and heating it to react, so that a molybdenum-doped copper tungstate precursor film is formed on the surface of the substrate;
[0010] S3: Cooling the reaction kettle, washing, drying and heat treating the substrate, and forming the copper tungstate photoanode film on the surface of the substrate;
[0011] The molybdenum inside the copper tungstate photoanode film is gradient doped, and the molybdenum content gradually increases from the surface of the film away from the substrate to the surface of the film close to the substrate.
[0012] A technical solution in the method for preparing a copper tungstate photoanode film of the present invention has at least the following beneficial effects:
[0013] The copper tungstate photoanode film prepared by the method is gradient doped with molybdenum. The introduction of molybdenum helps to reduce the conductive position of copper tungstate, and the continuous concentration change makes a continuous gradient energy level structure appear in the film bulk phase. Therefore, the performance of the doped film is greatly improved compared with the undoped and uniformly doped copper tungstate photoanode materials. Under simulated sunlight (AM 1.5G, 100mW·cm -2 ) Electrode potential 1.23V vs. RHE Photocurrent density reached 1.1mA·cm -2 (0.2 mol / L potassium phosphate buffer solution) and 1.9 mA cm -2 (1mol / L glycerol + 1mol / L potassium phosphate buffer solution).
[0014] The mechanism of gradient doping of molybdenum is:
[0015] In the preparation process of molybdenum-doped copper tungstate photoanode film, the differences in solubility, activity and deposition kinetics of metal ions in the solution work together to form a gradient doping of molybdenum. Specifically:
[0016] Under the reaction pH conditions, the binding tendency of molybdenum ions and copper ions is relatively strong, which makes molybdenum preferentially deposited on the conductive substrate. Under the condition of the same or similar concentrations of tungsten and molybdenum, copper tungstate (molybdenum) acid has a tendency of more molybdenum and less tungsten in the initial film formation. As the reaction proceeds, the formation of copper tungstate or copper molybdate will reduce the pH of the reaction system, and the binding of tungsten ions and copper ions will be enhanced. At the same time, the continuous decrease in molybdenum concentration also reduces the reaction rate of copper molybdate. The reaction rate of copper tungstate is higher than that of copper molybdate, so that the increase in the ratio of tungsten to molybdenum concentration during the deposition process tends to form copper tungstate (CuWO4), thereby achieving the effect of molybdenum gradient doping. Because the atomic radii of tungsten and molybdenum are similar and their properties are similar, the two can replace each other, so the physical phase of the final material formed is close to copper tungstate, but the film has a gradient distribution structure with increasing molybdenum concentration from the surface to the inner layer.
[0017] According to some embodiments of the present invention, the copper source includes at least one of copper sulfate, copper nitrate, copper chloride and copper acetate.
[0018] According to some embodiments of the present invention, the tungsten source includes at least one of sodium tungstate, ammonium tungstate, ammonium metatungstate, and tungstic acid.
[0019] According to some embodiments of the present invention, the molybdenum source includes at least one of ammonium tetramolybdate, ammonium heptamolybdate, ammonium octamolybdate, sodium molybdate, and molybdic acid.
[0020] According to some embodiments of the present invention, the pH of the solution is 3-5.
[0021] The pH of the solution can be adjusted using copper salt anionic acids such as hydrochloric acid, nitric acid, and sulfuric acid and cationic bases such as ammonia and sodium hydroxide solutions.
[0022] According to some embodiments of the present invention, the temperature of the temperature-raising reaction is 140-180°C.
[0023] According to some embodiments of the present invention, the temperature of the temperature-raising reaction is any one of 140°C, 150°C, 160°C, 170°C, 180°C, or a range formed by any two of them, such as 150°C to 170°C.
[0024] According to some embodiments of the present invention, the temperature rising reaction time is 2 to 12 hours.
[0025] According to some embodiments of the present invention, the time of the temperature rising reaction is any value among 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or a range formed by any two of them, such as 5h to 10h.
[0026] According to some embodiments of the present invention, the heat treatment temperature is 450-600°C.
[0027] According to some embodiments of the present invention, the temperature of the heat treatment is any one of 450°C, 500°C, 550°C, 600°C, or a range formed by any two of them, such as 500°C to 550°C.
[0028] According to some embodiments of the present invention, the heat treatment time is 1 to 4 hours.
[0029] According to some embodiments of the present invention, the time of the temperature rising reaction is any one of 1 h, 2 h, 3 h, 4 h, or a range formed by any two of them, such as 2 h to 3 h.
[0030] According to some embodiments of the present invention, the concentration of copper in the solution is 10×10 -3 ~200×10 -3 mol / L.
[0031] According to some embodiments of the present invention, in the solution, the atomic ratio of copper:tungsten:molybdenum is 0.9-1.15:0.6-0.95:0.05-0.4.
[0032] According to some embodiments of the present invention, the tungsten content in the copper tungstate photoanode film gradually decreases from the surface of the film away from the substrate to the surface of the film close to the substrate.
[0033] The second aspect of the present invention provides a copper tungstate photoanode film, which is prepared by the preparation method of the first aspect of the present invention.
[0034] One of the technical solutions of the present invention regarding the copper tungstate photoanode film has at least the following beneficial effects:
[0035] By gradient doping with molybdenum, this method can effectively adjust the electronic structure and energy band structure inside the copper tungstate film. Gradient doping causes the concentration of molybdenum to gradually increase from the surface of the film to the substrate side, forming a continuous gradient energy level structure. This structure significantly improves the separation efficiency of electrons and holes, reduces the probability of electron recombination, and thus improves the photoelectric catalytic performance of the film, especially the photocurrent density and the overall photoelectric conversion efficiency.
[0036] The introduction of molybdenum lowers the conductive band position of copper tungstate, making the electron transport of the film more efficient. The gradient doping of molybdenum helps to form a uniform electric field distribution, thereby promoting the rapid migration of electrons inside the film and reducing the energy loss during charge transfer. This not only improves the conductivity of the film, but also enhances its performance in the photoelectric catalytic process.
[0037] In simulated sunlight (AM 1.5G, 100mW·cm -2 ), the photocurrent density of the copper tungstate photoanode film prepared by this method reached 1.1 mA cm -2 (0.2 mol / L potassium phosphate buffer solution) and 1.9 mA cm -2 (1mol / L glycerol + 1mol / L potassium phosphate buffer solution). These data show that the photoelectric performance of the gradient Mo-doped film is significantly improved compared to the undoped or uniformly doped CuWO 4 photoanode film, indicating that it has higher efficiency in photocatalytic applications.
[0038] This method uses a simple solution method to prepare copper tungstate photoanode film, and achieves gradient doping of molybdenum by adjusting the pH value and reaction conditions. Compared with the traditional uniform doping method, this process is not only easy to implement, but also can efficiently control the distribution of molybdenum to form the desired gradient structure, avoiding the complicated preparation process.
[0039] By precisely controlling the pH and reaction conditions in the solution, it is possible to achieve a gradient change in the molybdenum content at different locations of the film, which provides more room for further optimization of material properties. The molybdenum doping concentration can be adjusted according to specific application requirements to optimize the photoelectrocatalytic performance of copper tungstate films under different conditions.
[0040] Therefore, the gradient doping of molybdenum in the copper tungstate photoanode film prepared by this method can significantly improve its photoelectrocatalytic performance, including increasing the photocurrent density, improving the electron transfer efficiency, increasing the film stability and improving the photoelectric conversion efficiency. These beneficial effects make the film have broad prospects in applications such as photocatalysis and water decomposition.
[0041] The third aspect of the present invention provides the use of the copper tungstate photoanode film of the second aspect of the present invention in photoelectrocatalytic water decomposition.
[0042] The application of copper tungstate photoanode film in photoelectrocatalytic water decomposition has the following beneficial effects:
[0043] Copper tungstate photoanode film shows a high photocurrent density in the photoelectrocatalytic water splitting reaction. This is because copper tungstate has a suitable band gap (about 2.4eV), which can effectively absorb visible light in sunlight and convert it into photocurrent, promoting the water splitting reaction. Especially in the case of molybdenum gradient doping, the photocurrent density of the film is greatly improved, showing a higher photoelectrocatalytic efficiency compared to undoped or uniformly doped copper tungstate photoanode materials.
[0044] The efficiency of photocatalytic water splitting reaction is usually affected by the recombination of electron-hole pairs. Molybdenum gradient doping can optimize the electronic structure of copper tungstate photoanode film and improve the separation efficiency of electrons and holes. After gradient doping with molybdenum, a continuous energy level gradient is formed inside the film, which can effectively reduce the recombination probability of electrons and holes, allowing more photogenerated electrons to participate in the water splitting reaction and improve the catalytic efficiency.
[0045] Gradient doping of molybdenum reduces the conductive band position of copper tungstate and improves the conductivity of the film. The copper tungstate film doped with molybdenum has better electron transfer ability, which can effectively improve the charge migration efficiency and reduce the loss in charge transfer. This is crucial for photoelectrocatalytic water decomposition reaction, because improving the electron transfer efficiency can increase the rate of the catalytic reaction and improve the overall efficiency of the reaction.
[0046] Gradient doping of molybdenum allows the catalytic activity of copper tungstate film to be optimized by adjusting the molybdenum doping concentration. This gradient doping structure makes the catalytic performance present different characteristics in different parts of the film, providing more flexible regulation space. According to specific catalytic requirements, the efficiency of photoelectrocatalytic water splitting reaction can be further improved by controlling the degree of molybdenum doping and the structural design of the film.
[0047] The copper tungstate film has a strong light absorption capacity in the visible light region, and the light absorption range and efficiency of the film are further improved by gradient doping with molybdenum. The introduction of molybdenum not only changes the band gap structure of copper tungstate, but also may enhance the film's utilization of sunlight, especially in the visible light region, further improving the efficiency of the photoelectrocatalytic water splitting reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is the X-ray diffraction test result of the copper tungstate photoanode film prepared in Example 1.
[0049] Figure 2 This is a scanning electron microscope image of the copper tungstate photoanode film prepared in Example 1.
[0050] Figure 3 These are the element test results at different depths of the copper tungstate photoanode film prepared in Example 1.
[0051] Figure 4This is the band structure diagram of copper tungstate films with different Mo contents fitted by DFT.
[0052] Figure 5 The copper tungstate photoanode film prepared in Examples 1 to 4 was heated to 0.2 mol·L -1 Photocurrent spectrum tested in potassium phosphate buffer solution.
[0053] Figure 6 The copper tungstate photoanode film prepared in Example 5 was heated to 0.2 mol·L -1 Light and dark current spectra tested in potassium phosphate buffer solution.
[0054] Figure 7 The copper tungstate photoanode film prepared in Example 1 is 1 mol·L -1 Glycerol + 1 mol·L -1 Light-dark alternating current spectrum tested in potassium phosphate buffer solution.
[0055] Figure 8 The copper tungstate photoanode film prepared in Comparative Example 1 was -1 Photocurrent spectrum tested in potassium phosphate buffer solution.
[0056] Fig. 9 The copper tungstate photoanode film prepared in Comparative Example 2 was -1 Photocurrent spectrum tested in potassium phosphate buffer solution.
[0057] Fig.10 It is the AC impedance spectrum of comparative example 1 and embodiment 1 tested under light conditions. DETAILED DESCRIPTION
[0058] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0059] In a first aspect, some embodiments of the present invention provide a method for preparing a copper tungstate photoanode film, comprising the following steps:
[0060] S1: using a copper source, a tungsten source and a molybdenum source, preparing a solution containing copper, tungsten and molybdenum, and adjusting the pH of the solution;
[0061] S2: placing the substrate obliquely in a reaction kettle containing a solution, sealing it, and heating it to react, thereby forming a molybdenum-doped copper tungstate precursor film on the surface of the substrate;
[0062] S3: Cooling the reactor, washing, drying and heat treating the substrate, and forming a copper tungstate photoanode film on the substrate surface;
[0063] The molybdenum inside the copper tungstate photoanode film is gradient doped, and the molybdenum content gradually increases from the surface of the film far away from the substrate to the surface of the film close to the substrate.
[0064] It can be understood that the copper tungstate photoanode film prepared by the method is gradient doped with molybdenum. The introduction of molybdenum helps to reduce the conductive position of copper tungstate, and the continuous concentration change makes a continuous gradient energy level structure appear in the bulk phase of the film. Therefore, the performance of the doped film is greatly improved compared with the undoped and uniformly doped copper tungstate photoanode materials. Under simulated sunlight (AM 1.5G, 100mW·cm -2 ) Electrode potential 1.23V vs. RHE Photocurrent density reached 1.1mA·cm -2 (0.2 mol / L potassium phosphate buffer solution) and 1.9 mA cm -2 (1mol / L glycerol + 1mol / L potassium phosphate buffer solution).
[0065] The mechanism of gradient doping of molybdenum is:
[0066] In the preparation process of molybdenum-doped copper tungstate photoanode film, the differences in solubility, activity and deposition kinetics of metal ions in the solution work together to form a gradient doping of molybdenum. Specifically:
[0067] Under the reaction pH conditions, the binding tendency of molybdenum ions and copper ions is relatively strong, which makes molybdenum preferentially deposited on the conductive substrate. Under the condition of the same or similar concentrations of tungsten and molybdenum, copper tungstate (molybdenum) acid has a tendency of more molybdenum and less tungsten in the initial film formation. As the reaction proceeds, the formation of copper tungstate or copper molybdate will reduce the pH of the reaction system, and the binding of tungsten ions and copper ions will be enhanced. At the same time, the continuous decrease in molybdenum concentration also reduces the reaction rate of copper molybdate. The reaction rate of copper tungstate is higher than that of copper molybdate, so that the increase in the ratio of tungsten to molybdenum concentration during the deposition process tends to form copper tungstate (CuWO4), thereby achieving the effect of molybdenum gradient doping. Because the atomic radii of tungsten and molybdenum are similar and their properties are similar, the two can replace each other, so the physical phase of the final material formed is close to copper tungstate, but the film has a gradient distribution structure with increasing molybdenum concentration from the surface to the inner layer.
[0068] In combination with the first aspect, in some embodiments of the present invention, the copper source includes at least one of copper sulfate, copper nitrate, copper chloride, and copper acetate.
[0069] In combination with the first aspect, in some embodiments of the present invention, the tungsten source includes at least one of sodium tungstate, ammonium tungstate, ammonium metatungstate, and tungstic acid.
[0070] In combination with the first aspect, in some embodiments of the present invention, the molybdenum source includes at least one of ammonium tetramolybdate, ammonium heptamolybdate, ammonium octamolybdate, sodium molybdate, and molybdic acid.
[0071] In combination with the first aspect, in some embodiments of the present invention, the pH of the solution is 3-5.
[0072] The pH of the solution can be adjusted using copper salt anionic acids such as hydrochloric acid, nitric acid, and sulfuric acid and cationic bases such as ammonia and sodium hydroxide solutions.
[0073] In combination with the first aspect, in some embodiments of the present invention, the substrate is FTO glass.
[0074] The substrate is placed obliquely in a reaction vessel containing the solution, which means that the conductive side of the FTO glass is placed downward.
[0075] In combination with the first aspect, in some embodiments of the present invention, the temperature of the temperature-raising reaction is 140-180°C.
[0076] In combination with the first aspect, in some embodiments of the present invention, the temperature of the temperature-raising reaction is any one of 140°C, 150°C, 160°C, 170°C, 180°C or a range formed by any two of them, such as 150°C to 170°C.
[0077] In combination with the first aspect, in some embodiments of the present invention, the time of the temperature rising reaction is 2 to 12 hours.
[0078] In combination with the first aspect, in some embodiments of the present invention, the time of the temperature heating reaction is any value among 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or a range formed by any two of them, such as 5h to 10h.
[0079] In combination with the first aspect, in some embodiments of the present invention, the temperature of the heat treatment is 450-600°C.
[0080] In combination with the first aspect, in some embodiments of the present invention, the temperature of the heat treatment is any one of 450, 500°C, 550°C, 600°C or a range formed by any two of them, such as 500°C to 550°C.
[0081] In combination with the first aspect, in some embodiments of the present invention, the heat treatment time is 1 to 4 hours.
[0082] In combination with the first aspect, in some embodiments of the present invention, the time of the temperature rising reaction is any value of 1h, 2h, 3h, 4h or a range formed by any two of them, such as 2h to 3h.
[0083] In combination with the first aspect, in some embodiments of the present invention, the concentration of copper in the solution is 10×10 -3 ~200×10 -3 mol / L.
[0084] In combination with the first aspect, in some embodiments of the present invention, in the solution, the atomic ratio of copper: tungsten: molybdenum is 0.9-1.15: 0.6-0.95: 0.05-0.4.
[0085] In combination with the first aspect, in some embodiments of the present invention, the tungsten content in the copper tungstate photoanode film gradually decreases from the surface of the film away from the substrate to the surface of the film close to the substrate.
[0086] In the second aspect, some embodiments of the present invention provide a copper tungstate photoanode film, which is prepared by the preparation method of the first aspect of the present invention.
[0087] It should be noted that by gradient doping with molybdenum, this method can effectively adjust the electronic structure and energy band structure inside the copper tungstate film. Gradient doping causes the concentration of molybdenum to gradually increase from the surface of the film to the substrate side, forming a continuous gradient energy level structure. This structure significantly improves the separation efficiency of electrons and holes, reduces the probability of electron recombination, and thus improves the photoelectrocatalytic performance of the film, especially the photocurrent density and the overall photoelectric conversion efficiency.
[0088] The introduction of molybdenum lowers the conductive band position of copper tungstate, making the electron transport of the film more efficient. The gradient doping of molybdenum helps to form a uniform electric field distribution, thereby promoting the rapid migration of electrons inside the film and reducing the energy loss during charge transfer. This not only improves the conductivity of the film, but also enhances its performance in the photoelectric catalytic process.
[0089] Molybdenum doping helps improve the stability of copper tungstate photoanode films. The addition of molybdenum not only optimizes the conductivity of the film, but also effectively improves its anti-photocorrosion performance. Under long-term illumination and reaction environment, the presence of molybdenum helps to enhance the durability and stability of the film, making the film more durable and reliable in practical applications.
[0090] In simulated sunlight (AM 1.5G, 100mW·cm -2 ), the photocurrent density of the copper tungstate photoanode film prepared by this method reached 1.1 mA cm -2 (0.2 mol / L potassium phosphate buffer solution) and 1.9 mA cm -2 (1mol / L glycerol + 1mol / L potassium phosphate buffer solution). These data show that the photoelectric performance of the gradient Mo-doped film is significantly improved compared to the undoped or uniformly doped CuWO 4 photoanode film, indicating that it has higher efficiency in photocatalytic applications.
[0091] This method uses a simple solution method to prepare copper tungstate photoanode film, and achieves gradient doping of molybdenum by adjusting the pH value and reaction conditions. Compared with the traditional uniform doping method, this process is not only easy to implement, but also can efficiently control the distribution of molybdenum to form the desired gradient structure, avoiding the complicated preparation process.
[0092] By precisely controlling the pH and reaction conditions in the solution, it is possible to achieve a gradient change in the molybdenum content at different locations of the film, which provides more room for further optimization of material properties. The molybdenum doping concentration can be adjusted according to specific application requirements to optimize the photoelectrocatalytic performance of copper tungstate films under different conditions.
[0093] Therefore, the gradient doping of molybdenum in the copper tungstate photoanode film prepared by this method can significantly improve its photoelectrocatalytic performance, including increasing the photocurrent density, improving the electron transmission efficiency and improving the photoelectric conversion efficiency. These beneficial effects make the film have broad prospects in applications such as photocatalysis and water decomposition.
[0094] In a third aspect, some embodiments of the present invention provide an application of the copper tungstate photoanode film of the second aspect of the present invention in photoelectrocatalytic water decomposition.
[0095] It is understandable that the copper tungstate photoanode film exhibits a higher photocurrent density in the photoelectrocatalytic water decomposition reaction. This is because copper tungstate has a suitable band gap (about 2.4eV), which can effectively absorb visible light in sunlight and convert it into photocurrent, promoting the water decomposition reaction. Especially in the case of molybdenum gradient doping, the photocurrent density of the film is greatly improved, showing a higher photoelectrocatalytic efficiency compared to undoped or uniformly doped copper tungstate photoanode materials.
[0096] The efficiency of photocatalytic water splitting reaction is usually affected by the recombination of electron-hole pairs. Molybdenum gradient doping can optimize the electronic structure of copper tungstate photoanode film and improve the separation efficiency of electrons and holes. After gradient doping with molybdenum, a continuous energy level gradient is formed inside the film, which can effectively reduce the recombination probability of electrons and holes, allowing more photogenerated electrons to participate in the water splitting reaction and improve the catalytic efficiency.
[0097] Gradient doping of molybdenum reduces the conductive band position of copper tungstate and improves the conductivity of the film. The copper tungstate film doped with molybdenum has better electron transfer ability, which can effectively improve the charge migration efficiency and reduce the loss in charge transfer. This is crucial for photoelectrocatalytic water decomposition reaction, because improving the electron transfer efficiency can increase the rate of the catalytic reaction and improve the overall efficiency of the reaction.
[0098] Gradient doping of molybdenum allows the catalytic activity of copper tungstate film to be optimized by adjusting the molybdenum doping concentration. This gradient doping structure makes the catalytic performance present different characteristics in different parts of the film, providing more flexible regulation space. According to specific catalytic requirements, the efficiency of photoelectrocatalytic water splitting reaction can be further improved by controlling the degree of molybdenum doping and the structural design of the film.
[0099] The copper tungstate film has a strong light absorption capacity in the visible light region, and the light absorption range and efficiency of the film are further improved by gradient doping with molybdenum. The introduction of molybdenum not only changes the band gap structure of copper tungstate, but also may enhance the film's utilization of sunlight, especially in the visible light region, further improving the efficiency of the photoelectrocatalytic water splitting reaction.
[0100] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0101] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0102] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0103] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0104] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0105] Example 1
[0106] A copper tungstate photoanode film was prepared. The molybdenum inside the copper tungstate photoanode film was gradient doped, and the molybdenum content gradually increased from the surface of the film far away from the substrate to the surface close to the substrate.
[0107] The specific preparation method is:
[0108] D1. Prepare 60mL containing 3.75×10 -2 mol / L copper chloride, 2.5×10 -3 mol / L(NH4)6H2W 12 O 40 xH2O and 1.1×10 -3 mol / L(NH4)6Mo7O 24 ·4H2O solution, adjust the pH to 4.1 with 3mol / L HCl or ammonia water, and add it into the Teflon reactor liner.
[0109] D2. Place the clean FTO with the conductive surface facing downward in the inner container of step D1 and lean against the inner wall. Seal the reactor and keep it at 160° C. for 10 hours.
[0110] D3. After the reaction is completed, cool the reaction vessel, rinse the solution on the surface of the electrode film, and dry the sample. Treat the dried sample at 500℃ for 2 hours to obtain a gradient molybdenum (Mo)-doped copper tungstate film CuW x Mo 1-x O4.
[0111] Example 2
[0112] A copper tungstate photoanode film was prepared. The molybdenum inside the copper tungstate photoanode film was gradient doped, and the molybdenum content gradually increased from the surface of the film far away from the substrate to the surface close to the substrate.
[0113] The specific preparation method is:
[0114] D1. Prepare 60mL containing 3.75×10 -2 mol / L copper chloride, 2.8×10 -3 mol / L(NH4)6H2W 12 O 40 xH2O and 5.4×10 -4 mol / L(NH4)6Mo7O 24 4H2O solution, adjust the pH to 4.0 with 3mol / L HCl or ammonia, and add it into the Teflon reactor liner.
[0115] D2. Place the clean FTO with the conductive surface facing downward in the inner container of step D1 and lean against the inner wall. Seal the reactor and keep it at 160° C. for 10 hours.
[0116] D3. After the reaction is completed, the reaction vessel is cooled, the solution on the surface of the electrode film is rinsed, and the sample is dried. The dried sample is treated at 500°C for 2 hours to obtain a gradient molybdenum (Mo) doped copper tungstate film.
[0117] Example 3
[0118] A copper tungstate photoanode film was prepared. The molybdenum inside the copper tungstate photoanode film was gradient doped, and the molybdenum content gradually increased from the surface of the film far away from the substrate to the surface close to the substrate.
[0119] The specific preparation method is:
[0120] D1. Prepare 60mL containing 3.75×10 -2 mol / L copper chloride, 2.1×10 -3 mol / L(NH4)6H2W 12 O 40 xH2O and 1.6×10 -3 mol / L(NH4)6Mo7O 24 ·4H2O solution, adjust the pH to 4.3 with 3mol / L HCl or ammonia, and add it into the Teflon reactor liner.
[0121] D2. Place the clean FTO with the conductive surface facing downward in the inner container of step D1 and lean against the inner wall. Seal the reactor and keep it at 160° C. for 10 hours.
[0122] D3. After the reaction is completed, the reaction vessel is cooled, the solution on the surface of the electrode film is rinsed, and the sample is dried. The dried sample is treated at 500°C for 2 hours to obtain a gradient molybdenum (Mo) doped copper tungstate film.
[0123] Example 4
[0124] A copper tungstate photoanode film was prepared. The molybdenum inside the copper tungstate photoanode film was gradient doped, and the molybdenum content gradually increased from the surface of the film far away from the substrate to the surface close to the substrate.
[0125] The specific preparation method is:
[0126] D1. Prepare 60mL containing 3.75×10 -2 mol / L copper chloride, 1.9×10 -3 mol / L(NH4)6H2W 12 O 40 xH2O and 2.1×10 -3 mol / L(NH4)6Mo7O 24 ·4H2O solution, adjust the pH to 4.3 with 3mol / L HCl or ammonia, and add it into the Teflon reactor liner.
[0127] D2. Place the clean FTO with the conductive surface facing downward in the inner container of step D1 and lean against the inner wall. Seal the reactor and keep it at 160° C. for 10 hours.
[0128] D3. After the reaction is completed, the reaction vessel is cooled, the solution on the surface of the electrode film is rinsed, and the sample is dried. The dried sample is treated at 500°C for 2 hours to obtain a gradient molybdenum (Mo) doped copper tungstate film.
[0129] Example 5
[0130] A copper tungstate photoanode film was prepared. The molybdenum inside the copper tungstate photoanode film was gradient doped, and the molybdenum content gradually increased from the surface of the film far away from the substrate to the surface close to the substrate.
[0131] The specific preparation method is:
[0132] D1. Prepare 60mL containing 3.75×10 -2 mol / L copper sulfate, 2.5×10 -3 mol / L(NH4)6H2W 12 O 40 xH2O and 1.0×10 -3 mol / L(NH4)6Mo7O 24 ·4H2O solution, adjust the pH to 4.2 with 3mol / L HCl or ammonia, and add it into the Teflon reactor liner.
[0133] D2. Place the clean FTO with the conductive surface facing downward in the inner container of step D1 and lean against the inner wall. Seal the reactor and keep it at 160° C. for 10 hours.
[0134] D3. After the reaction is completed, the reaction vessel is cooled, the solution on the surface of the electrode film is rinsed, and the sample is dried. The dried sample is treated at 500°C for 2 hours to obtain a gradient molybdenum (Mo) doped copper tungstate film.
[0135] Comparative Example 1
[0136] A non-doped photoanode film was prepared, and the specific preparation method was as follows:
[0137] The 2.5×10 -3 mol / L(NH4)6H2W 12 O 40 xH2O and 1.1×10 -3 mol / L(NH4)6Mo7O 24 4H2O solution was replaced with 3.13×10 -3 mol / L(NH4)6H2W 12 O 40 ·xH2O solution to obtain undoped copper tungstate film.
[0138] Comparative Example 2
[0139] A uniform Mo-doped photoanode film was prepared. The specific preparation method is as follows:
[0140] 0.1971g (NH4)6H2W 12 O 40 ·xH2O, 0.0353g(NH4)6Mo7O 24 ·4H2O, 0.1705g copper chloride dihydrate and 0.1050g citric acid are added to a mixed solution of 1mL deionized water and 2mL anhydrous ethanol, and ultrasonically dispersed and dissolved for later use. Place the FTO on a gel coater, use a pipette to measure 120μL of the precursor solution and drop it on the FTO, and spin coat it at a speed of 3000r / min for 30s. After each layer of solution is spin-coated, place the FTO on a heating plate and heat treat it at 400℃ for 5 minutes. Repeat the spin coating and heating 6 times, then place the sample in a muffle furnace, heat it to 500℃ at 3℃ / min, and calcine it for 2h to obtain a uniform Mo-doped CuWO4 thin film electrode.
[0141] Performance Testing
[0142] The copper tungstate photoanode film prepared in Example 1 was subjected to X-ray diffraction analysis, and the results are as follows: Figure 1 shown.
[0143] from Figure 1 It can be seen that the diffraction peaks belong to copper tungstate and SnO2 of conductive glass, and the film sample has no other impurities.
[0144] The copper tungstate photoanode film prepared in Example 1 was observed by scanning microscope. Figure 2 shown.
[0145] from Figure 2 It can be seen that the microstructure of the film is mainly particle stacking.
[0146] The copper tungstate photoanode film prepared in Example 1 was subjected to elemental analysis, and the element distribution results at different depths were obtained by different sputtering times. Figure 3 shown.
[0147] It can be seen that from the surface to the inner layer of the film, the concentration of Mo gradually increases, and the concentration of tungsten gradually decreases. After reaching the conductive base layer, the Sn content increases rapidly, and Cu, W, and Mo all decrease rapidly, indicating that the film presents a gradient concentration distribution of tungsten and molybdenum;
[0148] Figure 4 The band structure of copper tungstate films with different Mo contents fitted by DFT. It can be seen that with the increase of Mo doping concentration, the conductive position of doped copper tungstate decreases, while the reference Figure 3The Mo concentration shown in the data increases gradually from the surface to the interior. The internal energy level structure of the embodiment of the present invention is as follows: Figure 4 The shown has a continuous gradient, which helps the separation of photogenerated electrons and holes.
[0149] Figure 5 The present invention embodiment 1-4 in 0.2mol·L -1 Photocurrent spectrum tested in potassium phosphate buffer solution.
[0150] Figure 6 Example 5 of the present invention at 0.2 mol·L -1 Light and dark current spectra tested in potassium phosphate buffer solution.
[0151] Figure 7 Example 1 of the present invention is 1 mol·L -1 Glycerol + 1 mol·L -1 Light-dark alternating current spectrum tested in potassium phosphate buffer solution.
[0152] Figure 8 The comparative example 1 of the present invention is 0.2 mol·L -1 Photocurrent spectrum tested in potassium phosphate buffer solution.
[0153] Fig. 9 The comparative example 2 of the present invention is 0.2 mol·L -1 Photocurrent spectrum tested in potassium phosphate buffer solution.
[0154] It can be seen that the gradient Mo-doped CuWO4 film ( Figure 5 ) photoelectrocatalytic performance (1.1 mA cm at 1.23 V vs. RHE) -2 ) is significantly better than the non-doped ( Figure 8 ) and uniform concentration Mo doping ( Fig. 9 ) copper tungstate film photoanode. At the same time, the gradient Mo-doped CuWO4 film also showed good performance in glycerol photoelectrooxidation (1.9 mA cm -2 (1.23V vs.RHE)( Fig. 9 ).
[0155] Fig.10 The AC impedance spectra of Comparative Example 1 and Example 1 tested under illumination conditions are given, from which it can be seen that the gradient Mo-doped CuWO4 film has a relatively better charge transfer capability.
[0156] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a copper tungstate photoanode film, characterized in that: The following steps are involved: S1: using a copper source, a tungsten source and a molybdenum source to prepare a solution containing copper, tungsten and molybdenum, and adjusting the pH of the solution; S2: placing the substrate obliquely in a reaction kettle containing the solution, sealing it, and heating it to react, so that a molybdenum-doped copper tungstate precursor film is formed on the surface of the substrate; S3: Cooling the reaction kettle, washing, drying and heat treating the substrate, and forming the copper tungstate photoanode film on the surface of the substrate; The molybdenum inside the copper tungstate photoanode film is gradient doped, and the molybdenum content gradually increases from the surface of the film away from the substrate to the surface of the film close to the substrate.
2. The preparation method according to claim 1, characterized in that: The copper source includes at least one of copper sulfate, copper nitrate, copper chloride, and copper acetate; and / or, the tungsten source includes at least one of sodium tungstate, ammonium tungstate, ammonium metatungstate, and tungstic acid; and / or, the molybdenum source includes at least one of ammonium tetramolybdate, ammonium heptamolybdate, ammonium octamolybdate, sodium molybdate, and molybdic acid.
3. The preparation method according to claim 1, characterized in that: The pH of the solution is 3-5.
4. The preparation method according to claim 1, characterized in that: The temperature of the temperature-raising reaction is 140-180° C.; and / or the time of the temperature-raising reaction is 2-12 hours.
5. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment is 450-600° C.; and / or the time of the heat treatment is 1-4 hours.
6. The preparation method according to claim 1, characterized in that: In the solution, the concentration of copper is 10×10 -3 ~200×10 -3 mol / L.
7. The preparation method according to claim 1, characterized in that: In the solution, the atomic ratio of copper:tungsten:molybdenum is 0.9-1.15:0.6-0.95:0.05-0.
4.
8. The preparation method according to any one of claims 1 to 7, characterized in that The tungsten content inside the copper tungstate photoanode film gradually decreases from the surface of the film away from the substrate to the surface of the film close to the substrate.
9. A copper tungstate photoanode film, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. Use of the copper tungstate photoanode film as claimed in claim 9 in photoelectrocatalytic water decomposition.